2019
DOI: 10.25251/skin.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an evidence-based decision point for clinical use of the 31-gene expression profile test in cutaneous melanoma

Abstract: Treatment plans for cutaneous melanoma are based upon individual risk of recurrence. Decisions made post-diagnosis include recommendation for a sentinel lymph node biopsy (SLNB), followed by management decisions such as surveillance, frequency of follow-up, and interdisciplinary consultations including possible adjuvant therapy use. These have traditionally been guided by clinicopathologic factors, but discordance exists, as a substantial number of melanoma deaths occur in patients diagnosed with disease consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Prior studies have validated its ability to determine the risk of local/distant recurrence and sentinel lymph node positivity to assist in clinical decisionmaking. [1][2][3] The 31-GEP test is reimbursable under Medicare, certified by the Clinical Laboratory Improvement Amendments (CLIA), and was ordered over 16,000 times during 2019. 1,4 Given the increasingly widespread use of 31-GEP, the purpose of this study was to assess the professional understanding, opinions, and clinical usage of the 31-GEP test by dermatologists.…”
mentioning
confidence: 99%
“…Prior studies have validated its ability to determine the risk of local/distant recurrence and sentinel lymph node positivity to assist in clinical decisionmaking. [1][2][3] The 31-GEP test is reimbursable under Medicare, certified by the Clinical Laboratory Improvement Amendments (CLIA), and was ordered over 16,000 times during 2019. 1,4 Given the increasingly widespread use of 31-GEP, the purpose of this study was to assess the professional understanding, opinions, and clinical usage of the 31-GEP test by dermatologists.…”
mentioning
confidence: 99%
“…6 These recommendations include use of 31-GEP in any patient with melanoma with negative SLNB, as well as patients with T1 tumors (including tumors with a depth Յ0.3 mm with adverse features) for SLNB decision guidance. 6,9 A recent study surveyed 181 dermatology clinicians (approximately 50% dermatologists practicing for more than 20 years) and found that 22% of clinicians would order 31-GEP testing on nonulcerated melanomas with a Breslow depth of 0.26 mm, and 78% would order testing on tumors with a depth of 0.50 mm. 4 Neither NCCN nor American Academy of Dermatology guidelines include 31-GEP testing as part of routine care for any melanoma.…”
mentioning
confidence: 99%
“…However, publications have encouraged changes in diagnostic and management protocols based on 31-GEP testing results . These recommendations include use of 31-GEP in any patient with melanoma with negative SLNB, as well as patients with T1 tumors (including tumors with a depth ≤0.3 mm with adverse features) for SLNB decision guidance . A recent study surveyed 181 dermatology clinicians (approximately 50% dermatologists practicing for more than 20 years) and found that 22% of clinicians would order 31-GEP testing on nonulcerated melanomas with a Breslow depth of 0.26 mm, and 78% would order testing on tumors with a depth of 0.50 mm .…”
mentioning
confidence: 99%